Superalloys 2008 (Eleventh International Symposium) 2008
DOI: 10.7449/2008/superalloys_2008_417_423
|View full text |Cite
|
Sign up to set email alerts
|

Surface Effects on Low Cycle Fatigue Behavior in IN718 Alloy

Abstract: Superalloys used in gas turbine engine rotating components require superior low cycle fatigue (LCF) properties, but often, the intrinsic LCF capability of the rotor, as determined by laboratory specimen tests, is limited by presence of fine particles such as carbides, borides and ceramic inclusions, as well as, pores, voids, and large grains in the alloy. Further, manufacturing processes such as turning, milling, and broaching can limit LCF life if they introduce surface damage and/or tensile residual stress. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 10 publications
2
14
0
Order By: Relevance
“…These results are consistent with the effect of compressive residual stresses introduced by surface treatment like shot peening and characterized in the literature [2,[6][7][8][9][10]. The presence of compressive residual stresses under the anomalies generates a beneficial effect on the fatigue performance of the material.…”
Section: Influence Of Residual Stresses On the Fatigue Lifesupporting
confidence: 93%
See 2 more Smart Citations
“…These results are consistent with the effect of compressive residual stresses introduced by surface treatment like shot peening and characterized in the literature [2,[6][7][8][9][10]. The presence of compressive residual stresses under the anomalies generates a beneficial effect on the fatigue performance of the material.…”
Section: Influence Of Residual Stresses On the Fatigue Lifesupporting
confidence: 93%
“…In some cases, their introduction result from processing and/or machining operation as recently discussed and analysed by Bhowal et al for Direct Aged (DA) 718 alloy [2]. Many studies [2][3][4][5] were undertaken to determine the effect of machining parameters on the surface integrity and the creation of residual stresses on nickel-based superalloy. Authors indicate that the use of a worn tool or abusive machining conditions results in poor surface integrity and contributes to create harmful residual stresses.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…This is similar to results reported by others showing a high compressive stress level. For example, Bhowal et al reported of compressive stresses after shot peening of Inconel 718 of approximately − 1200 MPa which improved the fatigue strength 5-10 times the one of a machined surface with tensile residual stresses [36]. Such high compressive residual stresses are desirable from a fatigue perspective and were further reported by Chen et al who showed that shot peening of Inconel 718 greatly influences the surface performance and increases the fatigue limits by introducing high compressive residual stresses [27].…”
Section: Effects On the Residual Stress Statementioning
confidence: 91%
“…During the finishing treatment of nickel alloys, the physical properties of the surface layer are changed. As a result of the conducted shot peening of the Inconel 718 alloy, compressive stresses are deposited on the surface layer [19,20], which translates into the increased fatigue strength [1,3]. The stress depth and its value depends on the machining time, material of the balls and the distance at which the workpiece is located from the nozzle [19].…”
Section: Introductionmentioning
confidence: 99%